EXPERIENCE OF DEVELOPING PROFESSIONAL STANDARDS OF ACADEMIC STAFF IN THE HIGHER EDUCATIONAL INSTITUTIONS OF THE GREAT BRITAIN - Skyba, Yurii (Educological discourse, 2018)
The article outlines the reasons for the development of the National Framework for Professional Standards of Scientists and Teachers of Great Britain, which was associated with the need to improve the quality of teaching by academic and teaching staff, its use as a diagnostic tool for their certification, and for development their professional competence depending on the role of teachers and / or improvement of teaching practice for career advancement. The evolution of the National Framework of Professional Standards of Scientific and Teachers of Higher Educational Institutions of Great Britain is disclosed; a significant improvement of the new National Framework of Professional Standards for academic and teaching staff has been established, both for purposes and fields of activity, knowledge and professional values.